STRATEGI DINAS PERINDUSTRIAN, PERDAGANGAN DAN KOPERASI (PERINDAGKOP) KABUPATEN NAGAN RAYA DALAM MENGEMBANGKAN USAHA KECIL DAN MENENGAH - Adam Sani (Universitas Teuku Umar, 2017)
The purpose of this research is to know the strategy of Industry, Trade and Cooperative Office in developing small and medium enterprises in Nagan Raya District and to know the obstacles faced by Industry, Trade and Cooperative Office in developing small and medium enterprises in Nagan Raya District. The method used in this research is descriptive qualitative with the source data taken through observation, interview and documentation. Disperindagkop Nagan Raya District in the development of Small and Medium Enterprises namely guidance and Counseling, covering (a) the development of various products, (b) improvement of product quality, (c) licensing counseling, (d) marketing, education and training, covering (a) management Capital and finance, (b) production techniques, (c) entrepreneurship, Provision of Assistance, covering (a) capital assistance, (b) equipment aid and Evaluation and supervision. There are also inhibiting factors, such as internal resistor factors from Disperindagkop Nagan Raya District that is the level of quality and quantity of apparatus is still limited, the amount of budget funds for UKM development program. And supporting facilities and infrastructure are still inadequate. External inhibiting factors are the level of quality of human resources is still limited, lack of interest in trying. The authors provide suggestions that can be utilized by relevant agencies Increasing the frequency of meetings with UKM and the growing interest of young people to the importance of wrestle in the field of business. Keywords: Strategy, Development, UKM, Disperindagkop.